2018
DOI: 10.1080/1040841x.2017.1418285
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanisms ofHelicobacter pyloriand its dual target precise therapy

Abstract: Helicobacter pylori drug resistance presents a significant challenge to the successful eradication of this pathogen. To find strategies to improve the eradication efficacy of H. pylori, it is necessary to clarify the resistance mechanisms involved. The mechanisms of H. pylori drug resistance can be investigated from two angles: the pathogen and the host. A comprehensive understanding of the molecular mechanisms of H. pylori resistance based on both pathogen and host would aid the implementation of precise ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 163 publications
1
61
1
7
Order By: Relevance
“…30 Therefore, the 87 and 91 mutations might not only affect protein structure but also directly impair the binding between protein and DNA Hideki Mori et al showed double-mutate strain (N87 and D91 or N87 and A88) in gyrA evoked high-level resistance in H. pylori. 36 The MIC values of antibiotic-resistant strains with gyrA mutation were significantly higher than those of nonmutant strains, indicating that gyrA mutation was associated with high LVXresistant level. 33 Regarding 99 and 143 sites, our results also demonstrated the binding with LVX were weakened after mutation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…30 Therefore, the 87 and 91 mutations might not only affect protein structure but also directly impair the binding between protein and DNA Hideki Mori et al showed double-mutate strain (N87 and D91 or N87 and A88) in gyrA evoked high-level resistance in H. pylori. 36 The MIC values of antibiotic-resistant strains with gyrA mutation were significantly higher than those of nonmutant strains, indicating that gyrA mutation was associated with high LVXresistant level. 33 Regarding 99 and 143 sites, our results also demonstrated the binding with LVX were weakened after mutation.…”
Section: Discussionmentioning
confidence: 91%
“…Seck et al also found no gyrA mutation in some LVX-resistant strains, 34 suggesting other resistance-related mechanisms such as efflux pump, 35 membrane permeability, autophagy, globular transformation, and even new resistant genes. 36 The MIC values of antibiotic-resistant strains with gyrA mutation were significantly higher than those of nonmutant strains, indicating that gyrA mutation was associated with high LVXresistant level. Hideki Mori also displayed that the significant difference of the MICs of sitafloxacin between gyrA mutation-negative and -positive H. pylori strains.…”
Section: Discussionmentioning
confidence: 91%
“…The genotypic determination of antimicrobial resistance has made possible the elucidation of the molecular mechanisms of H. pylori resistance to antimicrobials such as clarithromycin, tetracycline, metronidazole, among others [22][23][24][25][26][27]. Resistance to clarithromycin has resulted from 3 points mutations A2142G, A2142C, and A2143G in 23S rDNA in the gene encoding the peptidyl transferase enzyme especially in the V domain (mutations too named like A2146C, A2146G, and A2147G) [28].…”
Section: Introductionmentioning
confidence: 99%
“…48,49 The goal of medicine precision is identify which regimen is best for an individual patient. 53 Thus, our results suggest in the future that personalized therapy could be ideal for H pylori eradication under controlled conditions, considering personalized medicine could avoid an increase in adverse effects, such as lack of patient's compliance and increase in antibiotic resistance.…”
Section: Discussionmentioning
confidence: 72%